2023
DOI: 10.1039/d2cs00395c
|View full text |Cite
|
Sign up to set email alerts
|

Unnatural helical peptidic foldamers as protein segment mimics

Abstract: This review highlights the research progress in the past 10 years in exploring unnatural foldamers as protein helical segment mimics, by giving some representative examples and discussing the current challenges and future perspectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 261 publications
0
6
0
Order By: Relevance
“…The comparative conformational studies undertaken in the current work with fluorinated and non-fluorinated peptides using 2D-NMR, SC-XRD, and CD studies will be helpful in the rational design of fluorine-incorporated small molecules as drugs (aromatic rings are common motifs in drugs) [27,28] to artificial peptides (foldamers) as biomimetic molecules. [29][30][31][32][33][34][35][36]…”
Section: Introductionmentioning
confidence: 99%
“…The comparative conformational studies undertaken in the current work with fluorinated and non-fluorinated peptides using 2D-NMR, SC-XRD, and CD studies will be helpful in the rational design of fluorine-incorporated small molecules as drugs (aromatic rings are common motifs in drugs) [27,28] to artificial peptides (foldamers) as biomimetic molecules. [29][30][31][32][33][34][35][36]…”
Section: Introductionmentioning
confidence: 99%
“…To tackle these challenges, researchers have come up with peptide mimetics, for instance, synthetic helical foldamers bearing synthetic peptidic backbones with desirable or new biological functions. 11 Over the past years, our group has focused on the development of peptidic foldamers-sulfonyl-γ-AApeptides 12 and explored their functions as helical peptide mimetics with either left or right handedness for protein recognition or modulation of PPIs. [13][14][15][16][17][18][19][20][21][22][23][24] Our research findings to date have shown that sulfonyl-γ-AApeptides possess excellent helical propensity, favourable resistance to enzymatic degradation, abundant chemical diversity, and increased cell permeability, which enhance their potential as an alternative strategy to helical peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Supramolecular assembly, which utilizes randomly oriented molecules to form ordered functional structures based on a bottom-up approach, is a ubiquitous process in nature. As a representative class of biomimetic smart molecules, foldamers can spontaneously assemble into elaborate three-dimensional structures, which could be crucial to realize specific functions. A variety of organic foldamers, such as peptidomimetics and aromatic amide oligomers, have been reported with a propensity to assemble into folded structures via cooperative hydrogen bond and π–π interactions. These foldamers have wide applications in stimuli-responsive luminescent materials, ion channels, , catalysis, , and so on. , …”
Section: Introductionmentioning
confidence: 99%